Geological and Geotechnical Challenges Faced during Excavation of the Underground Powerhouse and Head Race Tunnel for Mangdechhu Project, Bhutan, India (Hydro Nepal: Journal of Water, Energy and Environment, 2018)
Not available.HYDRO Nepal JournalJournal of Water, Energy and Environment Issue: 23Year: 2018